FLEXURAL VIBRATION OF A MULTI-DISK ROTOR WITH DIFFERENT BOUNDARY CONDITIONS (Sciences & Technologie. B, Sciences de l'ingénieur, 2017)
In this paper the flexural vibrations of a multi-disk rotor is considered. The analysis is made for the rotor when it is simply-simply supported and when it is free-simply supported.This is done for the asymmetric undamped case where critical speeds and responses to synchronous and asynchronous forces are determined and compared.